Association of ultra-processed food consumption and MRI-based carotid plaque characteristics: results from the Atherosclerosis Risk in Communities study - Shutong Du; Valerie K. Sullivan; Kunihiro Matsushita; Seamus P. Whelton; Lyn M. Steffen; Michael Fang; Lawrence J. Appel; Bruce A. Wesserman; Casey M. Rebholz (American Journal of Preventive Cardiology)
Background: Ultra-processed food and beverage consumption has been linked with adverse cardiovascular events, yet its association with sub-clinical disease remains less explored. Methods: A total of 768 white participants from the Carotid MRI visit (2004–2005) in the Atherosclerosis Risk in Communities (ARIC) study were included. Participants were selected via stratified sampling to enrich for informative plaques while preserving population-level reference. Dietary intake was assessed using a 148-item food frequency questionnaire, with items classified by Nova processing levels. Carotid artery imaging was conducted via MRI and analyzed with semiautomated software. Weighted multivariable linear and logistic regression models assessed associations between quartiles of ultra-processed food intake and plaque measurements or lipid core presence. Results: Higher ultra-processed food consumption was associated with unfavorable carotid plaque characteristics. Participants in quartile 4 of ultra-processed food consumption had greater total wall volume (standardized difference: β = 0.28, 95% CI, 0.07, 0.49), total lipid core volume (β = 0.55, 95% CI, 0.17, 0.92), maximum segmental wall thickness (β = 0.23, 95% CI, 0.01, 0.45), and maximum lipid core area (β = 0.49, 95% CI, 0.12, 0.86) vs. quartile 1. Replacing one daily serving of ultra-processed food with unprocessed or minimally processed food was associated with a reduction in total wall volume (β = -0.02, 95% CI, -0.05, -0.00). Conclusions: Higher intake of ultra-processed food was associated with a greater burden of atherosclerotic plaque in the carotid artery. Our findings support the need for further investigation into the potential impact of ultra-processed food on atherosclerotic changes and the underlying mechanisms by which it may increase the future risk of cardiovascular disease development.